Why Do Closed-End Bond Funds Exist? An Additional Explanation for the Growth in Domestic Closed-End Bond Funds - Elton, Edwin J.; Gruber, Martin J.; Blake, Christopher R.; Shachar, Or (Journal of Financial and Quantitative Analysis, 2013)
This paper provides a new explanation for why closed-end bond funds coexist along with otherwise identical open-end bond funds. Closed-end bond funds offer investors the opportunity to leverage their fixed income investment at very low borrowing rates and are attractive to investors for this reason. We find that differences in leverage are reflected in the discount on closed-end bond funds in a manner consistent with the advantage of leverage.